Sovereign responsibility: An impossible solidarity - Molapo, Sepetla (HTS teologiese studies, 2022)
This article takes interest in solidarity as sovereign responsibility. Sovereign responsibility is a nonproductive form of care that emerges at the interface of order defined by a privileging of economy and a general economy defined by a return to order of life lost to death. It is this return that unveils the existence and operations of a general economy that order presupposes. The article locates its discussion of sovereign responsibility at two levels of relationality. Firstly, it situates its deliberations concerning sovereign responsibility in the family and among kin. Here it argues that as a form of solidarity, sovereign responsibility positions relations among kin as those of neighbours. Secondly, it shows that the question of the neighbour extends beyond kinship relations and into the realm of extra-kinship relations where others and strangers appear as neighbours. The overall argument of the article is that sovereign responsibility holds potential to facilitate an Afrocentred and counter-hegemonic response to the modern experience of alienation.Contribution: The modern experience of alienation, as well as how it can be challenged, are of interest to this article. The article recognises that numerous attempts have been made to try and address this problematic of alienation in modernity. What it claims has not been done is to engage that problem by taking Africa as an idea, and not just geography, seriously.